Managing global business in the Internet age - Hj. Ali, Juhary (Universiti Utara Malaysia, 2002)
The Internet Age and the Age of Globalisation is an important phenomenon in determining the New World Order. The economic activities, in particular, are no longer limited and confined to geographical, culture, languages, and political ideological boundaries.Today the world is said to be “borderless” and is rich with challenges and opportunities that are beneficial to the world.The information revolution in the Internet Age reshapes the structure and conduct of business and delivery of education and services on a global scale.This phenomenon will present new challenges and opportunities to all segments of the society.This book is categorised to Information Technology and The Internet, E-Commerce, Pricing and Transaction Cost, E-Learning and Distance Education, Marketing, International Trade and Cross-Cultural Issues, and Knowledge Management, Human Resources and Management (HRM) and Organisational Development.